Part Two: Debunking Prevailing Scholarly Views Pertaining to the Apostasy of Alleged Descendants of Shaykh Yusuf of Makassar - Najma Moosa (Al-Jami'ah Research Centre, 2020)
This paper is the second part of the two articles that discuss the controversy over the conversion of religion in the family of Shaykh Yusuf of Makassar after being exiled in South Africa during the Dutch colonial period at the end of the seventeenth century. This second part provides a critical and holistic analysis of the historical sources and historians’ initial arguments regarding the two families, Shaykh Yusuf and his in-laws. This paper also tries to review the main arguments of this paper so as not to get caught up in excessive demystification. In addition, it also discusses the implementation of the Dutch colonial policies as well as the issue of poverty and the practice of marriage policies that have contributed to settling this conversion problem.[Tulisan ini adalah bagian kedua dari dua tulisan yang membahas kontroversi pindah agama pada keluarga Syekh Yusus Makassar selepas diasingkan di Afrika Selatan pada masa kolonial Belanda akhir abad 17. Bagian kedua ini menyajikan analisis kritis dan holistik mengenai sumber-sumber sejarah dan argumen-argumen awal para sejarahwan mengenai dua keluarga tersebut. Tulisan ini juga mencoba meninjau kembali argumen utama dari tulisan ini agar tidak terjebak dalam demistikasi yang berlebihan. Selain itu juga membahas pelaksanaan kebijakan kolonial Belanda serta soal kemiskinan dan praktik kebijaksanaan pernikahan yang berkontribusi mengendapkan persoalan konversi ini.]